2020
DOI: 10.9734/jocamr/2020/v12i130197
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Evaluation of Plant Parts of Rauwolfia Vomitoria

Abstract: Aims: This study was aimed at evaluating the antimicrobial activities of fractions of Rauwolfia vomitoria against some isolates including; Salmonella typhi, Escherichia coli, Candida albicans, Aspergillus niger, Microsporon canis, and Trichophyton rubrum. Methodology: Primary extraction was done on the dried and pulverized plant samples (leaves, barks, and root) using methanol, after which the crude extracts was fractionated using butanol, ethyl acetate, and n-hexane respectively. The samples were duly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Extracts of plants origin are reported to be rich in phytochemicals with antibacterial properties against a wide variety of micro-organisms. [23,24,25] Nevertheless, the effectiveness of plant extracts could be affected by the diffusion and solubility of the extracts in corrosive media for uptake by bacteria and adsorption into concrete matrix. At higher concentration it is suggested that the high efficiency could be as a result of higher dissolution of phytochemicals with time from the coating matrix into concrete and corrosive media.…”
Section: Inhibition Efficiencymentioning
confidence: 99%
“…Extracts of plants origin are reported to be rich in phytochemicals with antibacterial properties against a wide variety of micro-organisms. [23,24,25] Nevertheless, the effectiveness of plant extracts could be affected by the diffusion and solubility of the extracts in corrosive media for uptake by bacteria and adsorption into concrete matrix. At higher concentration it is suggested that the high efficiency could be as a result of higher dissolution of phytochemicals with time from the coating matrix into concrete and corrosive media.…”
Section: Inhibition Efficiencymentioning
confidence: 99%
“…The Genus Rauvolfia comprises several species including the African Rauvolfia vomitoria which are more distributed across the tropical regions of the World [19]. In Nigeria [20,21] as well as other tropical African countries [22]. Despite the enormous importance of the leaf in traditional medicine as well as its validated biological activities, there lacks well-documented evidence of any study on the pharmacognostic characters and peptidomic data of the leaf of this plant except partially for its root and that of the root of its co-generic species; R. serpentina [23,24,25,26].…”
Section: Rauvolfia Vomitoriamentioning
confidence: 99%